A Review on Fish Breeds and their Locality in Afghanistan - Farkhary, Sayed Ibrahim (Journal of Natural Sciences – Kabul University, 2023)
Afghanistan is a land-locked country but it has a diverse fish variety with more than 101 different species in 10 families. Most of species are belonging to Cyprinidae family with almost 50 species. There are three major drainage basins that include most of fish species in Afghanistan: The Kabul River basin draining to the Indus river of Pakistan includes majority (with 44 species), The Amu Darya draining to the Aral Sea is on second (with 29 species) and Helmand River basin draining to the Sistan terminal lakes on the Iranian border is on third (with 22 species). All of studies about fish biodiversity of Afghanistan have been done in 20th century and these studies did not cover all rivers of Afghanistan. Studies are needed to confirm that after many years and warfare, whether mentioned species are still exist? And there might be many other species that are not discovered yet.